Policy runs with the COMPAS model - Vuk, Goran (Proceedings from the Annual Transport Conference at Aalborg University, 2015)
This paper introduces an activity based (AB) traffic demand model for Copenhagen, called COMPAS. It is European first operational AB model of a discrete choice type. As an innovation we introduce the concept of Primary Family Priority Time (PFPT), which represents a high priority household decision to spend time together for in-home activities. Structural tests and estimation results identify two important findings. First, PFPT has a place high in the model hierarchy of day activity schedule submodels, and second, strong interactions exist between PFPT and the other day level activity components of the model system. Forecasts, for the year 2030, are generated for two case studies: a) a road pricing and congestion scenario by COMPAS and a comparison version of the model system that excludes PFPT, and b) an Autonomous Vehicle (AV) scenario. With respect to the first scenario, the COMPAS model system with PFPT is measurably less sensitive to a road pricing and congestion scenario than the comparison model system without PFPT. This is most evident in lower mode shift from car to other modes and smaller shift of car commutes away from the afternoon peak period. With respect to the Autonomous Vehicle scenario, we get for the morning peak traffic and home-work trips only, an increase of car trips by 8.2%.